Strategi Pengelolaan Destinasi Pariwisata Pada Objek Wisata Broken Beach Nusa Penida Kabupaten Klungkung - Supawetri, Ni Luh Putu Risa; Purnamaningsih, Putu Eka; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2022)
This study aims to determine the strategies applied in the management of tourism destinations at the Broken Beach Nusa Penida tourist attraction. In this research, the writer uses qualitative research with descriptive method. The analysis uses Strategic Planning theory and SWOT analysis techniques. The research findings indicate that the management of the Broken Beach tourist attraction is not optimal. This can be seen from several indicators that are not optimal, namely indicators of initiating and agreeing on a strategic plan, and indicators of formulating strategies to manage issues. The indicators that have been fulfilled are identifying the organizational mandate, clarifying the organization's mission and values, assessing the external environment of opportunities and threats, assessing the internal environment's strengths and weaknesses, identifying strategic issues facing the organization, creating an effective and efficient organizational vision. Keywords: Strategic Planning, SWOT Analysis, Tourism